Single-cell genomics reveals features of a Colwellia species that was dominant during the Deepwater Horizon oil spill - Mason, Olivia U.; Han, James; Woyke, Tanja; Jansson, Janet K. (Frontiers in Microbiology, 2014)
During the Deepwater Horizon (DWH) oil spill in the Gulf of Mexico a deep-sea hydrocarbon plume developed resulting in a rapid succession of bacteria. Colwellia eventually supplanted Oceanospirillales, which dominated the plume early in the spill. These successional changes may have resulted, in part, from the changing composition and abundance of hydrocarbons over time. Colwellia abundance peaked when gaseous and simple aromatic hydrocarbons increased, yet the metabolic pathway used by Colwellia in hydrocarbon disposition is unknown. Here we used single-cell genomics to gain insights into the genome properties of a Colwellia enriched during the DWH deep-sea plume. A single amplified genome (SAG) of a Colwellia cell isolated from a DWH plume, closely related (avg. 98% 16S rRNA gene similarity) to other plume Colwellia, was sequenced and annotated. The SAG was similar to the sequenced isolate Colwellia psychrerythraea 34H (84% avg. nucleotide identity). Both had genes for denitrification, chemotaxis and motility, adaptations to cold environments, and a suite of nutrient acquisition genes. The Colwellia SAG may be capable of gaseous and aromatic hydrocarbon degradation, which contrasts with a DWH plume Oceanospirillales SAG genome which encoded non-gaseous n-alkane and cycloalkane degradation. The disparate hydrocarbon degradation pathways are consistent with hydrocarbons that were abundant at different times in the deep-sea plume; first, non-gaseous n-alkanes and cycloalkanes that could be degraded by Oceanospirillales, followed by gaseous, and simple aromatic hydrocarbons that may have been degraded by Colwellia. These insights into the genomic properties of a Colwellia species, which were supported by existing metagenomic sequence data from the plume and DWH contaminated sediments, help further our understanding of the successional changes in the dominant microbial players in the plume over the course of the DWH spill.